AKTIVITAS PENGANGKAPAN RADIKAL POLIFENOL DALAM DAUN TEH - Rohdiana, Dadan (Indonesian Journal of Pharmacy, 2001)
Ability of free radical scavengers of various tea extracts (black tea, fermented tea; green tea , unfermented tea; oolong dan pouchong tea semifermented tea) was studied. The scavenging effects on active oxygen decreased in order semifemented tea > unferfmnted tea > fennented lea. Antioxidant activity on tea often might related wthi catechin presence. Catechin activity as antioxidant estabilished. Several epidemilogical and phartnacokgical research shown that catechin had a strongly antioxidan activity. (-)-epigallocatechin gallate (EGCG) and (-)-epicatechin gallate (ECG) are the major catechin of ~ tea This compounds had a strongly scavenging activity on free radical such as superoxide, hydrogen superoxide, DPPH and peroxynitdte. This review aim to exploited~ tea Oyphenols ability as free radicals sw vengers Key word: antioxidant activity, active oxygen, scavenging effect